Customers, partners and rights-holders: School evaluations on websites. Issue 3 (1st January 2016) - Carlbaum, Sara
Abstract : This paper explores how evaluation, which has expanded at all levels of school governance across Europe, shapes parental roles by studying how local school governors and schools in Sweden represent evaluation to parents on their websites. Websites are prime locations for public communications and are useful for exploring the functions of evaluations intended for parental use. In recent decades, parental influence over school has increased through 'choice and voice' options, while the role of evaluations has continued to expand in school governance. Evaluations construct social roles, identities and relations and, as such, are constitutive of the social world and our place in it. By drawing on Dahler-Larsen's concept of "constitutive effects", the discursive implications of evaluation are discussed. The dominant type of evaluation represented on websites is performance data used for accountability and informed school choice purposes. Parents are primarily positioned as customers who exert influence through choice and exit options, reinforcing the almost unquestioned norm of parental right to educational authority. Representations of evaluation differ depending on local political majority, school performance, and public versus independent provider; as such, they are not hegemonic but tend to strengthen the position of parents as individual rights-holders, marginalising forms of collective action.